Increasing the Productivity of SMEs based on partnerships: How to Achieving Competitive Advantage - Purwanto, Setiyo; Wuryandari, Nur Endah Retno (Teumulong: Journal of Community Service, 2024)
Efforts to develop Small and Medium Enterprises (SMEs) promoted by Dian Nusantara University (UNDIRA) in Situgadung Village, Tangerang through a partnership with IKRT Family Care Plus is here as a solution to answer the challenges faced by SMEs, especially in the fields of management and technology with products which are certified. This Community Service Program provides technological support through better production tools to increase productivity, financial management training, and online marketing to strengthen human resource competence. UNDIRA's involvement in financial management training, and manufacturing production machines with process automation technology is expected to increase the productivity of IKRT Family Care Plus, create employment opportunities, improve the quality of environmentally friendly products, and increase sales. This program can also become a partnership model for other educational institutions, to strengthen the competitiveness of MSMEs and stimulate the people's economy.